Pengaruh Ukuran Perusahaan, Leverage, Kepemilikan Institusional Dan Good Corporate Governance Terhadap Pengungkapan Corporate Social Responsibility Pada Perusahaan Manufakture Sektor Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2017 - Selly Towira; Mesrawati; Dessika Kosasih; Devi Chandra; Andriany Layandy; Ria Mariana (Jurnal Akuntansi Bisnis Eka Prasetya : Penelitian Ilmu Akuntansi, 2020)
The purpose of this study was to determine the effect of Firm Size, leverage, Institutional Ownership, and GCG disclosure on CSR on Food Manufacture sector companies listed on the Indonesia Stock Exchange period 2014-2017. The used of mixed methods. Types of research are descriptive and explanatory survey. The overall population in this study were 51 Food Manufacture sector companies listed on the Indonesia Stock Exchange period 2014-2017 and 18 companies used as samples. Classis assumtion test used before multiple linear regression analysis methods. The results of this studies indicate Firm Size negatively affect on the CSR disclosure in Food Manufacture sector companies listed on the Indonesia Stock Exchange period 2014-2017. Leverage, Institutional Ownership, and GCG has positive influence on the CSR disclosure in Food Manufacture sector companies listed on the Indonesia Stock Exchange period 2014-2017. Is study are classic assumption test and hypothesis testing with multiple regression analysis. The results of this study indicate that firm size, leverage, institutional ownership and GCG has positive influence on the CSR disclosure disclosure in Food Manufacture sector companies listed on the Indonesia Stock Exchange period 2014-2017.